2012
DOI: 10.1038/nature11589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a rudimentary neural crest in a non-vertebrate chordate

Abstract: Neural crest arises at the neural plate border, expresses a core set of regulatory genes, and produces a diverse array of cell types including ectomesenchyme derivatives that elaborate the vertebrate head1,2. The evolution of neural crest has been postulated as a key event leading to the appearance of new cell types that fostered the transition from filter feeding to active predation in ancestral vertebrates3. However, the origin of neural crest remains controversial, since homologous cell types have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
217
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(231 citation statements)
references
References 31 publications
12
217
0
2
Order By: Relevance
“…First, the lateral neural borders in nematodes, fly, annelids, and urochordates show conserved neural patterning where the medial portion of the Msx/vab-15-expressing domain gives rise to the CNS whereas the lateral portion generates the PNS. Second, their lateral PNS progenitors exhibit several key features of vertebrate PNS progenitors, such as migration and differentiation into mechanosensory neurons (7,8,10,13,34). Our genetic analysis also shows that Msx/vab-15 specifies these PNS progenitors in nematodes, fly (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…First, the lateral neural borders in nematodes, fly, annelids, and urochordates show conserved neural patterning where the medial portion of the Msx/vab-15-expressing domain gives rise to the CNS whereas the lateral portion generates the PNS. Second, their lateral PNS progenitors exhibit several key features of vertebrate PNS progenitors, such as migration and differentiation into mechanosensory neurons (7,8,10,13,34). Our genetic analysis also shows that Msx/vab-15 specifies these PNS progenitors in nematodes, fly (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Unlike the vertebrate NPB and neural crest, the molecular mechanism underlying the specification of worm lateral neuroblasts still remains largely unknown after years of genetic study (33,40,41). Our systematic expression profiling of 90% conserved transcription factors in C. elegans revealed that three NPB specifiers (Msx/vab-15, Pax3/7/pax-3, and Zic/ ref-2) are coexpressed in worm lateral neuroblasts and that Msx/ vab-15 expression is more lateral than that of Pax3/7/pax-3 and Zic/ref-2, like their expression patterns in neural borders of vertebrates, urochordates, amphioxus, and likely annelids (7,8,11,13,24). Furthermore, we showed that Msx/vab-15 regulates the differentiation of PNS progenitors in worm and fly, similar to its critical role in specifying PNS lineage in urochordates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B 281: 20141729 delamination and migration (figure 2b) [97,102]. Although the presence of a neural crest in ascidians has been debated [103], a recent study of Ciona embryos demonstrates that the neural crest melanocyte regulatory network pre-dated the divergence of tunicates and vertebrates, but the cooption of mesenchyme determinants, such as Twist, into neural plate ectoderm is absent (figure 2b) [104]. That is, the neural crest evolved as a vertebrate-specific GRN innovation.…”
Section: (Iii) Vertebratamentioning
confidence: 99%
“…Some migratory cells in the vicinity of the nerve cord were shown to migrate and develop into pigment cells, but these were not migrating from edges of the neural plate [50]. In addition, it was found that ectopic expression of Twist could induce some cells to migrate away from the Ciona neural tube [51]. However, tunicates are evolving rapidly.…”
Section: (B) Neural Crestmentioning
confidence: 99%